Sharing knowledge and field pratice for recycling road and road related materials: the Direct-Mat project - Antunes, M. L. (2010)
In order to facilitate the share of national experiences on dismantling and recycling of road and road related materials, a three-year European project was initiated in January 2009, within the UE 7th Framework Programme Transport.   This project involves partners from 15 participating countries for a budget of 1,2 million Euros and its main outcome will be the construction of a European Web database and the preparation of best practice guides on DIsmantling and RECycling Techniques for road MATerials (“DIRECT-MAT”).   The database compiles and displays the extensive existing and already validated research and jobsite data; the best practice guides on the dismantling and recycling of different types of materials will be issued from the benchmarking of national practices.   The intention is that the project results shall support the daily work of practitioners, researchers and standardisation bodies, by assisting CEN technical committees in incorporating scientifically-based material requirements on recycled road materials into European standards, increasing the confidence of stakeholders and practitioners in the use of recycled road products, an setting up a shared view of road material research needs to improve the coordination of national research.   The purpose of this paper is to describe the concept, objectives, benefits, partners and organisational strategy of the project and present the results achieved during the first year.